Denitrification contributes to N2O emission in paddy soils - Xiang, Hua; Hong, Yiguo; Wu, Jiapeng; Wang, Yu; Ye, Fei; Ye, Jiaqi; Lu, Jing; Long, Aimin (Frontiers in Microbiology, 2023)
Denitrification is vital to nitrogen removal and N2O release in ecosystems; in this regard, paddy soils exhibit strong denitrifying ability. However, the underlying mechanism of N2O emission from denitrification in paddy soils is yet to be elucidated. In this study, the potential N2O emission rate, enzymatic activity for N2O production and reduction, gene abundance, and community composition during denitrification were investigated using the 15N isotope tracer technique combined with slurry incubation, enzymatic activity detection, quantitative polymerase chain reaction (qPCR), and metagenomic sequencing. Results of incubation experiments showed that the average potential N2O emission rates were 0.51 ± 0.20 μmol⋅N⋅kg–1⋅h–1, which constituted 2.16 ± 0.85% of the denitrification end-products. The enzymatic activity for N2O production was 2.77–8.94 times than that for N2O reduction, indicating an imbalance between N2O production and reduction. The gene abundance ratio of nir to nosZ from qPCR results further supported the imbalance. Results of metagenomic analysis showed that, although Proteobacteria was the common phylum for denitrification genes, other dominant community compositions varied for different denitrification genes. Gammaproteobacteria and other phyla containing the norB gene without nosZ genes, including Actinobacteria, Planctomycetes, Desulfobacterota, Cyanobacteria, Acidobacteria, Bacteroidetes, and Myxococcus, may contribute to N2O emission from paddy soils. Our results suggest that denitrification is highly modular, with different microbial communities collaborating to complete the denitrification process, thus resulting in an emission estimation of 13.67 ± 5.44 g N2O⋅m–2⋅yr–1 in surface paddy soils.